Effect of cataract phacoemulsification on irido-corneal angle parameters and anterior chamber depth in a swept-source optical coherence tomography study – open vs primary closed-angle eyes comparison study - Kurowska, Anna; Szaflik, Jerzy; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Purpose : The aim of the study was to compare the change in irido-trabecular angle configuration and anterior chamber depth after cataract phacoemulsification using swept-source anterior segment optical coherence tomography in eyes with open and primary closed anterior chamber angle. Material and methods : 211 eyes (157 patients) divided into 2 groups according to anterior segment optical coherence tomography findings and clinical data: open-angle group (n = 127) and closed-angle group (n = 84) were enrolled. Angle parameters: AOD500, TISA500 and TIA in 4 quadrants, ITC index and central anterior chamber depth were measured preoperatively and at 6 months postoperatively. Results : The mean values of all angle parameters were significantly smaller in closed-angle group before and after surgery (p< .001). They increased significantly in all eyes (p< .05), but the difference between the groups was not statistically significant. ITC index before and after surgery was 78.2% and 19.7% in closed-angle eyes (p< .001) and 32.94% and 0.0% in open-angle eyes (p< .001), respectively. The anterior chamber depth increased significantly after surgery in both groups (p< .001) with bigger change observed in closed-angle group (mean difference 0.32 mm, p< .001). Conclusions : Cataract surgery opens and increases the width of the irido-corneal angle to the same extent in closed- and open-angle groups, so the angle remains more narrow in initially closed-angle eyes. ITC index in a swept-source anterior segment optical coherence tomography is a useful tool for the quantitative evaluation of angle closure area before and after cataract surgery. Postoperative change in anterior chamber depth differed significantly between the closed- and open-angle eyes.